Modeling international investment decisions for financial holding companies - Trappey, Charles V.; Shih, Tsui-Yii; Trappey, Amy J. C. (My University, 2007)
This research analyzes the internationalization process model developed by Johanson and Vahlne and derives two integer programming investment decision models that consider the risk attitudes of investment firms. Johanson and Vahlne's model provides a starting point for building a model that suits the investment approach and decision making process of financial holding companies. In practice, when firms make an international investment decision, there is a need for a model that can generate outputs based on financial measures such as profit, investment returns, and tolerable levels of risk. Thus, in this paper, Johanson and Vahlne's concepts are studied and financial managers are interviewed to derive models that match the investment decision procedures of the firms. The model helps firms manage the risks of their investments and derive accurate investment strategies based on investment objectives and constraints. (c) 2006 Published by Elsevier B.V.
Keywords: market commitment; market knowledge; internationalization process model; investment decision model; integer programming; financial holding companies